(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the theoretical and methodological foundations for researching the issues of ensuring social security in the context of geopolitical conflicts. It provides a socio-philosophical analysis of ensuring social security under such conditions and explores the future tasks related to this issue. Additionally, the social-philosophical aspects of the problems of ensuring social security in the context of geopolitical conflicts are analyzed.